ANALISA PENERAPAN EVALUASI KINERJA PENGENDALIAN PERSEDIAAN OBAT MELALUI SISTEM INFORMASI AKUNTANSI PADA INSTALASI FARMASI RUMAH SAKIT SANTOSA - Silvia Ratna Dewi; Vicky Dzaky Cahaya Putra (JASS (Journal of Accounting for Sustainable Society), 2024)
Santosa Hospital is one type A hospital that has a pharmaceutical installation with various types of drug supplies. This study aims to determine the application of inventory control performance evaluation through accounting information systems. Drug inventory accounting information system is needed by pharmaceutical installations for inventory control, one of which is avoiding drug stock shortages. This study used descriptive qualitative research methods and used data collection techniques with interviews and observations. The results showed that the Drug Inventory Accounting Information System at the Santosa Hospital Pharmacy Installation was running well but there was a weakness, namely the lack of evaluation related to the use of pettycash and purchases to partner hospitals that have PKS to meet routine drug needs.